Indicadores de qualidade do leite de vacas criadas no sistema silvipastoril - Bolaños, Carmen Alicia Daza [UNESP] (2014)
The silvopastoral system is characterized by increasing the production of milk with a greater number of cows per hectare due to the higher amount of protein in the diet. In silvopastoral system cows are fed in addition to pasture, with small trees and shrubs. The aim of present study was determinate the main indicators of milk quality and mastitis causal agents in cows bred on silvopastoral system. We evaluated the composition (fat, protein, lactose, solids, dry extract, nonfat dry and urea nitrogen), somatic cell count (SCC), total bacterial count (TBC), occurrence of clinical and subclinical mastitis, microbiological isolation, in vitro bacterial sensitivity profile and detection of antimicrobial/multiplication inhibitors residues in milk produced by cows raised in silvopastoral systems, as well as the bulk tank and churns in farms of Cauca Valley, Colombia. The concentration of the major constituents of milk were 3.24% fat, 3.27% protein, 4.40% lactose, 10.62% dry extract, 8.57% nonfat dry and 15.82 mg/dL urea nitrogen, while the bulk tank and churns was: 3.51% fat, 3.20% protein, 4.34% lactose, 11.72% dry extract, 8.47% nonfat dry and 14.57 mg/dL urea nitrogen. The cell count of the cows and the bulk tank were 141,252.75 CS/mL and 363,078.05 CS/mL, respectively. The TBC mean in cows and the bulk tank were 4,466.84 CFU/mL and 24.547.01 CFU/mL respectively. The main microorganisms isolated from the udder cows were Staphylococcus spp. (17%), Corynebacterium bovis (5%), Staphylococcus aureus (4%), Streptococcus spp. (3%), Streptococcus dysgalactiae (2%) and Staphylococcus hyicus (1%), while the bulk tank and churns were identified more often Streptococcus spp. (29%), Enterobacter cloacae (14%), Hafnia alveii (14%) and Streptococcus α-haemolytic (14%). Antimicrobial residues in cow milk and bulk or churn were detected in 30% and 86% respectively. The silvopastoral system is a good alternative to cow nutrition, however is important the ...